A Case of Placenta Percreta Managed with Sequential Embolisation Procedures - Shannon Armstrong-Kempter; Supuni Kapurubandara; Brian Trudinger; Noel Young; Naim Arrage (Case Reports in Obstetrics and Gynecology)
Background. The incidence of morbidly adherent placenta, including placenta percreta, has increased significantly over recent years due to rising caesarean section rates. Historically, abnormally invasive placenta has been managed with caesarean hysterectomy; however nonsurgical interventions such as uterine artery embolisation (UAE) are emerging as safe alternative management techniques. UAE can be utilised to decrease placental perfusion and encourage placental resorption, thereby reducing the risk of haemorrhage and other morbidities. Case. We describe one of the very few reported cases of placenta percreta which was successfully treated primarily with sequential artery embolisation. Our patient underwent four embolisation procedures over a period of 248 days, with no major morbidity or complications. Conclusion. Repeat UAE may be a beneficial primary management modality in cases of placenta percreta with bladder involvement.